The use of remdesivir outside of clinical trials during the COVID-19 pandemic - Vesa Halimi; Armond Daci; Nevenka Ridova; Irina Panovska-Stavridis; Milena Stevanovic; Venko Filipce; Aleksandar Dimovski; Aleksandra Grozdanova (Taylor & Francis Group, 2020)
With a scientific background from filoviruses, paramyxoviruses, SARS-CoV, and MERS-CoV, remdesivir entered into the COVID-19 battle to become one of the favorable therapeutic candidates with potential antiviral activity in the treatment of this disease. Globally, remdesivir was accessed and investigated through clinical research (clinical trials) and clinical practice (compassionate use, expanded access, early access scheme, and emergency use). Currently, remdesivir approval status differs between states. This paper aims to review and analyze regulatory approaches for accessing and investigating remdesivir, by communicating regulatory variability between countries in terms of terminology, modalities, and protocols.